PENGARUH PEMBERIAN PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) DENGAN DOSIS BERBEDA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium cepa L.) - Windy Djo Hau; Eka Citra Gayatri Kerihi, Charisal M. A. Manu, Nur Aini Bunyani (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This research was conducted in Kayu Putih Village, Qebobo District, Kupang City, from March 8 to May 8, 2025. The purpose of this study was to determine the effect of giving Plant growth promoting rhizobacteria (PGPR) with different doses on the growth and yield of shallots (Allium cepa L.). The method used in this study was the Randomized Block Design (RAK) method consisting of 4 levels of PGPR treatment, namely: PO (without PGPR), P1 (PGPR 10 ml / Liter of water), P2 (PGPR 20 ml / Liter of water) and P3 (PGPR 30 ml / Liter of water) and repeated 3 times so that there were 12 experimental units. Each research plot contained 12 plants with 4 plants as samples in each replication. The results showed that there was a significant effect of PGPR treatment on plant growth and yield. The treatment dose of 30 ml / Liter of water showed the best results on the growth and yield of shallots. The conclusion of this study is that P3 treatment with a dose of 30 ml gave the best results for all parameters